Negative Correlation between Cytoglobin Expression and Intracellular ROS Levels in Human Skin Keloid Fibroblasts - Fajri Marindra Siregar; Novi Silvia Hardiany; Sri Widia Azraki Jusman (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: In our previous study, we found higher cytoglobin (Cygb) expression in keloid than normal tissue. Cytoglobin is a new globin family protein which function is still being studied to date. The purpose of this research is to elucidate the function of Cygb in human skin keloid fibroblasts (KFs), especially its role in intracellular reactive oxygen species (ROS) levels.METHODS: The study was conducted on human skin KFs obtained from primary culture. Inhibition of Cygb expression was achieved by using siRNA targeting Cygb. We compared the relative expression of Cygb between treatment and control group, and its effect on intracellular ROS levels. Gene expression was measured using quantitative real-time polymerase chain reaction (qRT-PCR) while the ROS level counted by dichlorodihydrofluorescein diacetate (DCFHDA) assay.RESULTS: There was an increase in intracellular ROS levels in the small interfering RNA (siRNA) (+) Cygb group compared to control group (1.673 vs. 1.260; 1.773 vs. 1.393; 1.710 vs. 1.360; respectively). There is a negative correlation between Cygb expression and ROS level (p<0.05; r=-0.651).CONCLUSION: There is a negative correlation between Cygb expression and intracellular ROS levels, we suggest Cygb acts as a ROS scavenger in human skin KFs.KEYWORDS: skin keloid fibroblasts, cytoglobin, siRNA, ROS